Audit Sistem Informasi Pada Ts Beauty Center Menggunakan Framework Cobit 4.1 - Elok Elviana; Auralia Miffatul Jannah; Siti Mukaromah (Universitas Mercu Buana Yogyakarta, 2022)
Technological developments certainly bring positive things to a business or in the field of education. In addition, technological developments also facilitate various human work, such as the existence of information technology, but this must be balanced with an audit of the information system in order to prevent threats or losses at the TS Beauty center clinic. TS Beauty Center Clinic is located in Bojonegoro, because it is one of the well-known clinics. TS Beauty Center has a large number of customers spread from several areas, not only Bojonegoro. This clinic requires special skills and experience in the field of beauty for new employees. This study aims to determine the extent of the performance of the learning information system, namely the website for managing business processes at the TS Beauty Center and provide a recommendation for improved governance after knowing that there is an imbalance between the governance applied and the expected governance in accordance with the applied framework. The framework used in this research is COBIT version 4.1. Data collection techniques were carried out by means of interviews and questionnaires with resource persons and employees at the clinic that had been determined in accordance with the domain and Control Objective used. The data analysis method is carried out through the stages of determining the domain, determining the control process, determining indicators and mapping the level of maturity. The results of this study are to determine the maturity level of the website implementation at TS Beauty Center.